Faktor yang Mempengaruhi Minat Beli Konsumen Terhadap E-commerce GoFood di Era Covid-19 (Studi pada Masyarakat di Kota Bandung, Indonesia) - Puspaningrum, Rheyna Ayu (Asosiasi Ahli Administrasi Indonesia, 2022)
Due to the Covid-19 that has hit Indonesia since 2020, people's activities have become slightly hampered, especially to get goods from outside, one of which is food. Due to its practicality, many people use food ordering applications in this Covid-19 era, one of which is the GoFood application. In addition, there are still many factors that make someone use the GoFood application. Therefore, the purpose of this study is to find out what factors influence consumer purchase intention in GoFood in the Covid-19 era. This study uses a quantitative descriptive method with data analysis using the SPSS v.26 application. This study used a questionnaire measuring instrument and there were 148 GoFood users involved. The data analysis method used is factor analysis, validity test, reliability test, multiple linear regression analysis and correlation. The results of this study there are 4 factors that influence consumer purchase intention on GoFood, namely the perceived usefulness factor, the perceived ease of use factor, the security factor, and the information delivery factor.